Uji Metrologi Gerak Melingkar Pada Mesin CNC Milling Di Bengkel Mekanik Polmanbabel - Syahbilla, Muthiara; Husman, Husman; Erwansyah, Erwansyah (Jurnal Inovasi Teknologi Terapan, 2024)
The manufacturing industry now demands machining processes that are not only precise but also highly efficient. Computer Numerical Control (CNC) machines such as CNC milling have emerged as the answer to these challenges by enabling high-precision mass production. The State Polytechnic of Manufacturing in Bangka Belitung has an aging CNC Milling Machine Lagun MC-750, which has been in use since the establishment of the campus several years ago. The research is focused on metrological testing of circular motion on the CNC Milling machine in the Mechanical Workshop of Polmanbabel. The analytical method involves experimental studies encompassing machining processes, data collection of the results, and data analysis. The machining process is carried out using the CNC Milling Machine Lagun MC-750 with specific parameters such as cutting depth, cutting speed, and feed motion. The test specimens are made of S45C steel with dimensions Ø31.6 x 50 mm. The analysis of 12 specimens revealed a value of 146 μm for clockwise feed motion (G02) and 174 μm for counterclockwise feed motion (G03) for the other 12 specimens. These results fall within the tolerance grade IT 10. This indicates that the machine is suitable for processing workpieces within standard tolerances, as IT 10 is commonly used in general machining for interchangeable parts that can also be classified as highly precise work.